2023
DOI: 10.3389/fvets.2023.1072929
|View full text |Cite
|
Sign up to set email alerts
|

Understanding biosecurity behaviors of Australian beef cattle farmers using the ten basic human values framework

Abstract: IntroductionOn-farm biosecurity is an essential component of successful disease management in the beef cattle industry on an individual, regional, and national level. Participation in mandatory or voluntary assurance schemes, knowledge and trusted relationships have all been demonstrated to contribute to the development of behaviors that promote biosecurity. However, compliance with rules, socio-psychological relationships and knowledge-seeking behavior are all contingent upon the motivations and beliefs of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Without farmers fully comprehending biosecurity information, implementation is unlikely to be accurate [ 19 ] and, therefore, ineffective. Additionally, a farmer actively engaging in conversation with their vet allows for shared decision-making in the planning of biosecurity measures specific to that farm [ 37 , 52 ]. This also links to the theme of “Getting to know each other ” because an actively involved cattle farmer also offers information about the farm to their vet, which allows for the vet to tailor biosecurity to the specific farm in question.…”
Section: Discussionmentioning
confidence: 99%
“…Without farmers fully comprehending biosecurity information, implementation is unlikely to be accurate [ 19 ] and, therefore, ineffective. Additionally, a farmer actively engaging in conversation with their vet allows for shared decision-making in the planning of biosecurity measures specific to that farm [ 37 , 52 ]. This also links to the theme of “Getting to know each other ” because an actively involved cattle farmer also offers information about the farm to their vet, which allows for the vet to tailor biosecurity to the specific farm in question.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects covered in these courses include zoonotic agents, routes of transmission, diagnostics, and preventive approaches. Aspiring veterinarians are better equipped to handle zoonotic difficulties when they join the field by fostering zoonosis knowledge early in their education (Fountain et al 2023).…”
Section: Zoonotic Disease Surveillance and Diagnosis: Core Competenciesmentioning
confidence: 99%
“…Behavioral theories provide an explanation of the structural and psychological mechanisms believed to control behavior and changes in behavior [13]. Garza et al [14], Barnes et al [15], and Fountain et al [16] utilized behavioral theories such as the nudge theory and Schwartz's theory of basic human values to assess strategies used to increase compliance with animal biosecurity measures and disease reporting to safeguard the health of animals. These studies generally found that the use of behavioral theories was beneficial for increasing the range of interventions that could be considered to effect behavior change and increasing the effectiveness of interventions chosen to improve animal health.…”
Section: Introductionmentioning
confidence: 99%